Digitus ii manus : Digitus iv manus and its relationship with aerobic and anaerobic capacity among talented young footballers / Muhamad Ihram Johar - Johar, Muhamad Ihram (Faculty of Sport Science and Recreation, 2016)
The digit ratio refers to the proportion of length of the forefinger with respect to the ring finger. Digit ratio is controlled by the level of pre-birth testosterone and it is widely used to determine many things such as sporting ability. Digit ratio could be a crucial indicator in sport performance as it helps to show how aggressive a person is which may determine on how the athlete reacts to situations. The purpose of this study is to find the relationship between low digit ratio with aerobic and anaerobic capacity among talented young footballers. The subjects are from Kuala Lumpur Football Association (KLFA) Academy consist of male students age 1O.41±0.57 (years) with total number is 29 subjects (n=29). The result of Spearman's Rho shows that the correlation between low digit ratio and aerobic capacity performance which tested by using One Mile Run test (MRW) is r=0.37 where p=0.046. The result of Pearson's Correlation Coefficient shows that the correlation between low digit ratio and anaerobic capacity performance which tested by using 50 meters sprint test is r=-0.10 and p =0.606. In conclusion, this study can be used in classifying the athlete based on their nature of sport. Low digit ratio may be a good indicator in finding better sporting ability potential for the development of sport in Malaysia.